RESPON PERTUMBUHAN AWAL TANAMAN MENTIMUN MINI (Cucumis sativus L.) TERHADAP LAMA PERENDAMAN DAN KONSENTRASI GIBERELIN - Rahmatika, Widyana; Irawati, Titik; Putri Ayu C, Deva; D Andayani, Retno; Fitriyah, Nur; Mardiana, Yushi; SU, Pamuji (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
The demand for baby cucumbers for fresh and processed consumption requires fast-growing, uniform, and vigorous seeds from the early stages. According to data from the Ministry of Agriculture (2022), cucumber consumption in 2019 was 2,019 kg/capita/year, increasing to 2,190 kg/capita/year in 2020 and 2,297 kg/capita/year in 2021 (Alim AA, 2024). This demand will continue to grow as Indonesia's population increases. The success of this initial phase is greatly influenced by seed quality and pre-planting pretreatment techniques, such as soaking seeds in a gibberellin solution to accelerate germination and improve early growth. Soaking time and concentration are factors that can accelerate germination. The purpose of this study was to determine the interaction between soaking time and gibberellin concentration; to determine the appropriate soaking time and concentration for breaking the dormancy of baby cucumber seeds. The research design used was a factorial RAK with two factors: soaking time (3, 6, and 9 hours) and gibberellin concentration (100, 150, and 200 ppm). Thus, there were 9 treatment combinations, each repeated 3 times, resulting in 27 experimental units, each consisting of 20 seeds. To determine the treatment being tested, the data were analyzed using ANOVA. If the treatment had a significant effect, the Least Significant Difference Test was carried out. The results of the study showed that there was no interaction between treatments; an effect of gibberellin concentration on germination power and plant length; and an effect of soaking time on germination power, sprout length, plant length, and number of leaves. Keywords: Baby Cucumber; Concentration; Gibberellin; Soaking.